ONE-YEAR FOLLOW-UP OF PATIENTS TREATED FOR RHIZARTHROSIS WITH THE RegJoint™ IMPLANT - Denitsa Vasileva; Margarita Kateva; Georgi Petrov (Journal of IMAB, 2024)
Rhizarthrosis is the second most common degenerative disease of the hand, associated with pain, function disability, and impaired quality of life. The literature describes various operative techniques for the treatment of rhizarthrosis, but the outcomes of the effectiveness of RegJoint™ implant are still scarce. Purpose: The aim of this study is to determine the effectiveness of using the RegJoint™ implant in the operative treatment of rhizarthrosis and the subsequent recovery. Material and methods: In the period 2019-2023, a total of 48 patients diagnosed with rhizarthrosis (46 women and 2 men) of average age 61.4 (±3.2) years went for treatment through the clinical bases of UМHAT "Kaneff" - Ruse and UMHAT "SOFIAMED"- Sofia. All of them were operated with the bioabsorbable implant - RegJoint™, after which the thumb was immobilized using a fixation splint for 6 weeks. Their average hospital stay was 3.2 (±1.3) days, after which they underwent rehabilitation procedures for 6 months. Results: Functional capacity was assessed using the DASH test, and thumb movements were tested using the Kapanji score three times - preoperatively and at the end of the 6th and 12th postoperative months. The results at the end of 6 months and 1 year period show a significant improvement in terms of pain, swelling and functional status of the operated hand. Conclusion: The combined surgical intervention for the treatment of rhizarthrosis with a RegJoint™ implant, combined with adequate and timely physiotherapy, ensures a high-quality, fast and painless functional restoration of the thumb and the overall function of the hand.